Partial Purification and Characterization of Catalase from Banana Peels - Baghdad Science Journal (مجلة بغداد للعلوم)
Catalase (EC 1.11.1.6) is a well known enzyme which exists in almost all living creatures exposing to oxygen (such as plants, bacteria, and animals). It is a very necessary enzyme to protect the cell from oxidative detriment by reactive oxygen species (ROS). The aim of this study is the partial purification and characterization of Catalase enzyme from Banana peels. In this study, fresh banana peels are treated with 70 % ethanol ,further separated with chloroform ,water and ethyl acetate respectively .The supernatant of the enzymatic sample which is treated with chloroform is loaded into gel filtration column with Sephadex G-100 (1.0 x 90 cm) equilibrated with pH7 buffer media (phosphate buffer 0.1 M). Kinetic studies of the purified enzyme activity are measured and characterized .The maximal activity (26.04 units/mg) of catalase is observed with chloroform buffer extraction. The kinetics of catalase; Michalis constant Km and maximum velocity Vmax is determined using Linweaver- Burk plot, The Km value for catalase (434.7mM), Vmax (100 m mole min -1). Characterization results demonstrate that the optimal pH for activity is (7.6). And the optimal temperature for activity is 30?C .The present study indicates that Banana peels is a good source of catalase enzyme.